Pemetaan Strategi Promosi Penerimaan Mahasiswa Baru Menggunakan K-Means - Yanuar Wicaksono; Ujang Nendra Pratama; Siti Nurhasanah; Tri Utari Ramadania; Wulandari Juslan (Program Studi Sistem Informasi Fakultas Sains dan Teknologi, UIN Sunan Ampel Surabaya, 2021)
Universities need to have a special strategy to capture the target prospective students. The variety of promotional media needs to be analyzed so that the media distribution is right on target. The number of new student admissions in each year of a college is influenced by the promotional actions that have been carried out. Data mining is a method for finding useful new information from a large amount of data collection and can help in making decisions. The analysis of promotion strategies grouped with the K-means algorithm is expected to be used by the promotion team in determining promotion strategies to get new prospective students in accordance with the promotion target. Promotional media that can be accessed in all provinces are the internet and leaflets/posters. For close-range media in promoting higher education, benefits can still be taken such as school visits, educational exhibitions, newspapers, billboards/banners. However, for provinces outside Yogyakarta, there are promotion strategies that can be relied upon, namely student recommendations and alumni recommendations